Archeologia zachodniego Śródziemnomorza w Poznaniu – stan i perspektywy badań - Krueger, Michał (Folia Praehistorica Posnaniensia, 2013)
Polish Mediterranean archeology has been known almost exclusively for investigations carried out in the eastern Mediterranean. The aim of the article is to present research and teaching initiatives that have been undertaken by the researchers from Poznań within the western Mediterranean for the last ninety years. For the purpose, the basic research method has been to analyze the intellectual output in form of academic thesis, monographs and articles. The library exchange, the student participation in the western Mediterranean excavations, and the classes given in the field of Mediterranean archeology have been also analyzed. As a result, a growing interest in the archaeology of the western part of the Mediterranean in the academic community associated with the Institute of Prehistory, Adam Mickiewicz University in Poznań has been observed, and thus detailed reasons why research in the area should be developed were listed.